Helical Nanographenes Containing an Azulene Unit: Synthesis, Crystal Structures, and Properties - Ma, Ji; Fu, Yubin; Dmitrieva, Evgenia; Liu, Fupin; Komber, Hartmut; Hennersdorf, Felix; Popov, Alexey A.; Weigand, Jan J.; Liu, Junzhi; Feng, Xinliang (Angewandte Chemie International Edition, 2020)
Three unprecedented helical nanographenes (1, 2, and 3) containing an azulene unit are synthesized. The resultant helical structures are unambiguously confirmed by X-ray crystallographic analysis. The embedded azulene unit in 2 possesses a record-high twisting degree (16.1°) as a result of the contiguous steric repulsion at the helical inner rim. Structural analysis in combination with theoretical calculations reveals that these helical nanographenes manifest a global aromatic structure, while the inner azulene unit exhibits weak antiaromatic character. Furthermore, UV/Vis-spectral measurements reveal that superhelicenes 2 and 3 possess narrow energy gaps (2: 1.88 eV; 3: 2.03 eV), as corroborated by cyclic voltammetry and supported by density functional theory (DFT) calculations. The stable oxidized and reduced states of 2 and 3 are characterized by in-situ EPR/Vis–NIR spectroelectrochemistry. Our study provides a novel synthetic strategy for helical nanographenes containing azulene units as well as their associated structures and physical properties.
CRIS-Team Scopus Importer:2023-03-20
Keywords: azulene; helicenes; nanographenes; polycyclic aromatic hydrocarbons; Scholl reaction